Antibodies against Periodontal Microorganisms and Cognition in Older Adults. (April 2023) - Merchant, A.T.; Yi, F.; Vidanapathirana, N.P.; Lohman, M.; Zhang, J.; Newman-Norlund, R.D.; Fridriksson, J.
Introduction: Markers of poor oral health are associated with impaired cognition and higher risk of Alzheimer disease (AD) and thus may help predict AD. Objectives: The aim of this study was to evaluate the cross-sectional association between empirically derived groups of 19 IgG antibodies against periodontal microorganisms and cognition in middle-aged and older adults. Methods: The study population consisted of participants of the third National Health and Nutrition Examination Survey (NHANES III) (1988 to 1994), who were 60 y and older, among whom cognition and IgG antibodies against 19 periodontal microorganisms were measured (N = 5, 162). Results: In multivariable quantile regression analyses, the Orange-Red (Prevotella melaninogenica, Prevotella intermedia, Prevotella nigrescens, Porphyromonas gingivalis) and Yellow-Orange (Staphylococcus intermedius, Streptococcus oralis, Streptococcus mutans, Fusobacterium nucleatum, Peptostreptococcus micros, Capnocytophaga ochracea) cluster scores were negatively associated with cognition. A 1-unit higher cluster score for the Orange-Red cluster was associated on average with a lower cognitive score (β for 30th quantile = −0.2640; 95% confidence interval [CI], −0.3431 to −0.1848). Similarly, a 1-unit higher score for the Yellow-Orange cluster was associated with a lower cognitive score (β for 30th quantile = −0.2445; 95% CI, −0.3517 to −0.1372). Conclusion: Groups of IgG antibodies against periodontal microorganisms were associated with lower cognition among free living adults 60 years and older, who were previously undiagnosed with cognitive impairment. Though poor oral health precedes the development of dementia and AD, oral health information is currently not used, to our knowledge, to predict dementia or AD risk. Combining our findings with current algorithms may improve risk prediction for dementia and AD. Knowledge Translation Statement: IgG antibodies against periodontal microorganisms were associated with lower cognition among adults 60 years and older previously undiagnosed with cognitive impairment. Periodontal disease may predict cognition among older adults.